Trends and Characteristics of Spine Research From 2006 to 2015: A Review of Spine Articles in a High Impact General Orthopedic Journal. Issue 2 (15th January 2020) - Hollenberg, Alex M.; Bernstein, David N.; Baldwin, Avionna L.; Beltejar, Michael-John; Rubery, Paul T.; Mesfin, Addisu
Abstract : Study Design: Literature review. Objective: To determine characteristics and trends in published spine research over a recent decade in a high impact, general orthopedic surgery journal. Summary of Background Data: Recent trends in published spine research in a high-impact orthopedic surgery journal are unknown. Such knowledge could guide future research in the field. Methods: A comprehensive literature review of clinical and basic science spine articles published in The Journal of Bone & Joint Surgery from 2006 to 2015 was conducted. Articles were assessed for: title, year of publication, authorship, academic degrees of the authors, number of citations, institution of origin, and spine topic. Clinical articles were evaluated for: sex and race/ethnicity of the human subjects, level of evidence, and inclusion of patient-reported outcome measures (PROMs). Basic science articles were evaluated for: type of study (animal, cadaver, cell-based), sex of the animals, cadavers or cells studied (male, female, or male and female), and presence of sex-based reporting (defined as reporting of results by sex). Results: A total of 203 spine articles were evaluated from the 10-year study period. At least 35 validated or nonvalidated patient-reported outcome measures were utilized in clinical spine research. The most commonly reported PROMs were the Oswestry Disability Index (24.4%), Short Form-36 Health Survey (23.7%), and Visual Analog Scale for Pain (19.3%). The average level of evidence improved from 3.25 in 2006 to 2.60 in 2015. Only 13.2% of clinical spine articles reported the race/ethnicity of the subjects. Conclusion: A consensus regarding validated PROMs in spine research would be valuable. From 2006 to 2015, the level of evidence of spine articles in The Journal of Bone & Joint Surgery improved. Accurate and complete reporting of patient demographics is an area for improvement in spine research in light of studies demonstrating sex and race/ethnicity-related differences in clinical outcome after spine surgery. Level of Evidence: 5 Abstract : Supplemental Digital Content is available in the textThis comprehensive review article characterizes trends and characteristics in spine research in a high impact, general orthopedic surgery journal. There remains no consensus on which patient-reported outcome measure to use. There is room for improvement to include sex as a variable in clinical and basic science spine research.